SAT0225 A novel web based rheumatology educational resource – interactive computerised case studies for undergraduate teaching. (1st June 2001) - Wilson, AS; Kitas, GD; Bowman, SJ; Llewellyn, P; Bacon, PA; Young, SP
Abstract : Background: We have applied the principal that the undergraduate curriculum should have a reduced burden of factual information and learning through curiosity should be encouraged, 1 to the education of our rheumatology students. Objectives: We have applied advances in computer technology to develop a web based educational strategy and evaluated its use from the perspective of the student/user. Methods: A teaching needs assessment conducted on a cohort of 30 students prompted the development of a novel interactive case studies programme, accessible through the internet. This programme utilises active server page technology (TM) reading from a database of case study information (anonymised). The user can select predefined questions, perform a virtual physical examination and gain diagnostic information by requesting laboratory tests. The user is then required to make a diagnosis and select an appropriate treatment regimen for that patient. To introduce realism, performance is evaluated by an indication of the patients outcome and the financial expenditure incurred for their consultation. Usage data was collected from online questionnaire and by computer generated log file analysis. Results: All students agreed that computer based learning was a useful adjunct to traditional teaching and greater than 95% expressed strong support for the use of computerised case studies. All questionnaire respondents (n = 17) agreed that the computer programme was well organised, realistic and that they had learnt from the experience. Although this teaching aid is primarily aimed at our local teaching hospitals, log file analysis indicates that there have been 239 visits to the site (181 unique) from North America, Europe, Asia and Oceania, suggesting a widespread interest. Conclusion: This novel interactive web based programme, based on real life patient information, will serve as a teaching resource for our allied hospitals and introduce some variety into more formal teaching practices by promoting self-learning. The techniques employed could be adaptable to other situations which would benefit from increased user interaction and in a dispersed learning environment. Reference: General Medical Council report "Tomorrow's Doctors", 1993